2015
DOI: 10.1177/1049732315575712
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Recall and Reflections on Experiences Related to HPV Vaccination for Their Children

Abstract: Human papillomavirus (HPV) vaccination coverage remains suboptimal in the United States. We conducted in-depth interviews with parents of adolescents from an urban primary care center serving a low-income minority population to describe their experiences. We identified the following themes: (a) parents of unvaccinated children generally had not discussed the vaccine with providers and had low awareness; (b) among unaware parents, provision of brief information generally resulted in positive comments about the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 39 publications
3
34
0
Order By: Relevance
“…38,74 In the other approach, providers distinguished HPV vaccine from other adolescent vaccines by presenting it as an "optional" vaccine which was not required for school; this approach often involved a more lengthy discussion of risks and benefits as well as obtaining parental consent separately from, not along with, other vaccines. 38,74,77,79,91 Providers using the second approach reported higher levels of parental hesitancy and vaccine refusal or delay, but nevertheless felt obligated to mention the absence of school entry requirements for HPV vaccine and offer the option to delay vaccination in order to more closely coincide with sexual debut. 38,74 Providers who presented HPV vaccine as optional expressed the hope that this open-ended communication style would foster trust with vaccine hesitant parents, thereby encouraging the acceptance of other adolescent vaccines in the short term as well as HPV vaccine in the long term.…”
Section: Contentmentioning
confidence: 99%
See 4 more Smart Citations
“…38,74 In the other approach, providers distinguished HPV vaccine from other adolescent vaccines by presenting it as an "optional" vaccine which was not required for school; this approach often involved a more lengthy discussion of risks and benefits as well as obtaining parental consent separately from, not along with, other vaccines. 38,74,77,79,91 Providers using the second approach reported higher levels of parental hesitancy and vaccine refusal or delay, but nevertheless felt obligated to mention the absence of school entry requirements for HPV vaccine and offer the option to delay vaccination in order to more closely coincide with sexual debut. 38,74 Providers who presented HPV vaccine as optional expressed the hope that this open-ended communication style would foster trust with vaccine hesitant parents, thereby encouraging the acceptance of other adolescent vaccines in the short term as well as HPV vaccine in the long term.…”
Section: Contentmentioning
confidence: 99%
“…Quantitative and qualitative studies found that providers spent longer talking about HPV vaccine than other vaccines, 11,27,35,74,76,84 endorsed HPV vaccine less strongly than Tdap and meningococcal vaccines, 11,12,22,74,87 and often presented HPV vaccine as an "optional" vaccine vs. one that was "routine" or "required." 12,22,38,74,79,91 Finally, one study found that, among providers with a preferred order for discussing adolescent vaccines, over two-third preferred to discuss HPV vaccine last. 11 A fourth area of communication style considered the extent to which providers engaged parents and patients in discussion about HPV vaccination.…”
Section: Contentmentioning
confidence: 99%
See 3 more Smart Citations